Faktor yang Mempengaruhi Motivasi Belajar Siswa Penerima Kartu Indonesia Pintar di SMK Negeri 1 Batipuh - Syarifa Aulia; Reno Fernandes (Naradidik: Journal of Education and Pedagogy, 2022)
This study aims to determine learning motivation and the factors that influence the learning motivation of students receiving the Smart Indonesia Card at SMK Negeri 1 Batipuh. To analyze this research, the researcher uses the motivation theory proposed by Abraham Maslow about the hierarchy of human needs. This study uses a qualitative approach with the informant selection technique, namely purposive sampling with the number of informants as many as 19 people. Data was collected by means of observation, interviews, and documentation studies which were analyzed using data analysis techniques from Miles and Huberman (data reduction, data presentation, and drawing conclusions). The results showed that the learning motivation of students receiving the Smart Indonesia Card at SMK Negeri Batipuh had low learning achievement and there were still students who scored below the average and some even got the last rank.